John Jim and Clyde Cornect play and discuss music - Thomas, Gerald (1973)
John Jim et Clyde Cornect jouent le violon et la guitare ensemble. Mabel, Willie et Delma Cornect sont aussi présents. John Jim et Clyde jouent « Le Reel de Ste-Anne ». Ils discutent de la manière qu’on tient un violon et de la musique en générale. Ils parlent de la musique écossaise et jouent « Les vieux pis la vieille » et une autre chanson. -- John Jim and Clyde Cornect play violin and guitar together. Mabel, Willie et Delma Cornect are also present. John Jim and Clyde play "St. Anne's Reel" and discuss how to hold a violin. They talk about music generally and Scottish music in particular. They play "Les vieux pis une vieille" and another song. Transcription du F1758/C2387/CD-F1036 -- Transcript of F1758/C2387/CD-F1036